Model Pelibatan Masyarakat Dan Organisasi Lainnya Terhadap Lembaga Pendidikan - Neila Qonita; Muhammad Nazir; Septuri; Erjati Abbas; Afifuddin Ahmad Robbani (STIKes Ibnu Sina Ajibarang, 2024)
In general, community participation is often interpreted as a contribution of energy, money or goods in order to make a development program or project a success. In general, the relationship between schools and the community has a goal to be achieved, namely improving the quality of education, so that the community can feel the direct impact of improving the quality of education in the form of school progress.Library research or literature review is the research method used in this research. Several data and information were obtained regarding community involvement in educational institutions sourced from several journal articles and books as primary and secondary data sources. The school's relationship with the community includes the school's relationship with other schools, the school with the local government, the school with other agencies and departments, and the school with the community in general. First, educational relationships are cooperative relationships in terms of education/students, between teachers at school and parents in the family. Second, cultural relations are collaborative efforts between the school and the community which enable mutual development and development of the culture of the community where the school is located. Third, institutional relationships, namely cooperative relationships between schools and other official institutions or agencies, both private and government.